THE INFLUENCE OF AEROBICS WITH ELEMENTS OF MARTIAL ARTS ON THE DEVELOPMENT OF STRENGTH IN SENIOR STUDENTS - Shkolа , Olena; Kuzhimov , Bogdan (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2025)
The article considers the possibilities of using aerobics with elements of martial arts as an effective means of physical education of high school students with an emphasis on the development of strength qualities. The theoretical principles are determined, the impact of aerobic and combat exercises on the body of adolescents is analyzed, the physiological, psychological and social aspects of the training process are characterized. In conditions of martial law, special attention is paid to the formation of physical endurance, stress resistance and readiness of young people for unforeseen situations. Classes that combine dynamic aerobic exercises with applied elements of martial arts contribute not only to the improvement of physical indicators, but also to the development of discipline, willpower, responsibility. During the experimental study, the positive effect of such a technique on the development of strength in high school students, increasing motivation for physical education classes and improving the emotional state of students was confirmed. The results obtained can be used by physical education teachers, trainers and methodologists to improve educational programs in secondary education institutions.